2017
DOI: 10.1111/jgs.15050
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fracture in Women with Sarcopenia, Low Bone Mass, or Both

Abstract: Objective To determine if sarcopenia in the presence of low bone mineral density (BMD) increases the risk of clinical fractures in women compared to women with either sarcopenia or low BMD alone. Design Women’s Health Initiative (WHI) Observational and Clinical trials Setting 3 US Clinical Centers-Pittsburgh, PA, Birmingham, AL, and Phoenix/Tucson, AZ Participants 10,937 women (mean age 63.3 ± 0.07) with BMD measurements Measurements Sarcopenia was defined as appendicular lean mass values correcting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 30 publications
4
37
0
1
Order By: Relevance
“…A similar finding was observed in the Women’s Health Initiative,(33) and in the Health ABC study,(34) with the authors of this latter study suggesting that excess lean in excess of bone mass might be a pro-fracture state. However, this would seem to be at odds with the general adaptation of bone to muscle,(35) and excess lean mass or power over bone strength seems unlikely in older men (compared with younger athletes for example).…”
Section: Discussionsupporting
confidence: 84%
“…A similar finding was observed in the Women’s Health Initiative,(33) and in the Health ABC study,(34) with the authors of this latter study suggesting that excess lean in excess of bone mass might be a pro-fracture state. However, this would seem to be at odds with the general adaptation of bone to muscle,(35) and excess lean mass or power over bone strength seems unlikely in older men (compared with younger athletes for example).…”
Section: Discussionsupporting
confidence: 84%
“…Obesity was classified as body fat percentage of 42% or greater, as recommended for women aged 60 to 79, the category most closely corresponding to the WHI population . Following a previous WHI study, we defined sarcopenia using the residual method because it has been shown to have strong correlations with lower extremity function . Sarcopenia was defined as the lowest 20 th percentile of appendicular lean mass, accounting for height and body fat.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Furthermore, there is increasing evidence that any predictive value of ALM for fracture is substantially attenuated by consideration of femoral neck BMD. In a recent analyses, participants of the Women’s Health Initiative (WHI) were classified into mutually exclusive groups based on BMD and sarcopenia status (defined using appendicular lean mass values corrected for height and fat mass according to Newman et al[8])[9] Whereas low BMD was associated with increased risk of hip fracture, women with sarcopenia alone were at similar risk of hip fracture to non-sarcopenic women with normal BMD, suggesting that sarcopenia alone is not predictive of this outcome. In a further WHI study, appendicular lean mass was predictive of incident hip fracture amongst 872 participants 65 years or older who met Fried’s criteria for frailty, but this association did not remain statistically significant after adjusting for total hip BMD.…”
Section: Editorialmentioning
confidence: 99%